Quantum geometry, matrix theory, and gravity - Steinacker, Harold C. (Cambridge: Cambridge University Press, 2024)
"The volume provides an introduction to quantization in a broad context, and a systematic development of quantum geometry in Matrix Theory and string theory. It addresses advanced students and researchers in theoretical physics and mathematics, who are interested in quantum aspects of space-time and geometry in a physical context"--
Differentiable manifolds -- Lie groups and coadjoint orbits -- Quantization of symplectic manifolds -- Quantum spaces and matrix geometry -- Covariant quantum spaces -- Noncommutative field theory -- Yang-Mills matrix models and quantum spaces -- Fuzzy extra dimensions -- Geometry and dynamics in Yang-Mills matrix models -- Higher-spin gauge theory on quantum spacetime -- Matrix theory : maximally supersymmetric matrix models -- Gravity as a quantum effect on quantum spacetime -- Matrix quantum mechanics and the BFSS model.
Includes bibliographical references and index.
Keywords: Geometric quantization; Matrices; String models; Gravity -- Mathematical models